Community-based urban farming efficiency: A process engineering approach using mini greenhouses at RPTRA Rasamala, South Jakarta - Stefani, Megah; Putri, Bunga Cahya; Humayrah, Wardina (Community Empowerment, 2025)
Urban food security plays a crucial role in preventing stunting by providing independent nutritional resources. This community service program aims to enhance planting literacy and food production efficiency at RPTRA Rasamala, South Jakarta, through mini-greenhouse optimization. The implementation method employed a participatory approach integrated with process engineering techniques, specifically Value Stream Mapping (VSM) and Just-In-Time (JIT). The results demonstrated significant efficiency improvements, including a reduction in seedling growth time from 14 to 10 days, a 38% increase in the production cycle, and a 30% reduction in water and fertilizer usage. Furthermore, land utilization became more optimal through consistent planting schedules. Participants also showed increased technical understanding of organic planting media and the utilization of harvests for family nutrition. This program proves that integrating industrial management techniques into urban farming effectively increases food productivity while strengthening preventive measures against stunting in densely populated areas.